Advances in power boilers - Ozawa, Mamoru; Asano, Hitoshi (JSME series in thermal and nuclear power generation ;, 2021)
Advances in Power Boilers is the second volume in the JSME Series on Thermal and Nuclear Power Generation. The volume provides the fundamentals of thermal power generation by firstly analysing different fuel options for thermal power generation and then also by tracing the development process of power boilers in about 300 years. The design principles and methodologies as well as the construction, operation and control of power boilers are explained in detail together with practical data making this a valuable guide for post-graduate students, researchers, engineers and regulators developing knowledge and skill of thermal power generation systems. Combining their wealth of experience and knowledge, the author team presents recent advanced technologies to the reader to enable them to further research and development in various systems, notably combined cycles, USC and A-USC, as well as PFBC and IGCC. The most recent best practices for material development for advanced power system as well as future scope of this important field of technology are clearly presented, and environment, maintenance, regulations and standards are considered throughout. The inclusion of photographs and drawings make this a unique reference for all those working and researching in the thermal engineering fields. The book is directed to professional engineers, researchers and post-graduate students of thermal engineering in industrial and academic field, as well as plant operators and regulators.